Analyzing Students' Deductive Reasoning and Problem-Solving Skills in Algebraic Derivatives: The Role of Adversity Quotient (AQ) - Sinaga, Dewi Lestari; Surya, Edy; Mulyono, Mulyono; Lumbantobing, Happy (UIN Sunan Gunung Djati Bandung, 2025)
The purpose of this study was to analyze and describe the use of deductive reasoning and mathematical problem solving skills based on Adversity Quotient (AQ). The type of research used is qualitative descriptive research. The instruments in this study were deductive reasoning and problem solving ability test questions, and AQ questionnaires. The number of respondents in the study was 20 students. Respondents were divided into three types, namely Quitter, Camper, and Climber. The results showed that students with the Quitter type were only able to make calculations based on rules/formulas, but had not been able to draw conclusions and compile direct proof steps so that the problem solving indicators had not been achieved optimally. Students with the Camper type were able to make calculations based on rules or formulas, and were able to plan and implement plans in the problem solving aspect. Students with the Climber type were able to meet all indicators of deductive reasoning and problem solving in understanding problems, planning, implementing plans, and re-checking